Synthesis and properties of sulfonated poly(arylene ether ketone sulfone) copolymer. (April 2016) - Shen, Kunzhi; Dong, Bo; Wang, Yan; Lin, Liming; Chen, Zheng
A series of novel sulfonated poly(arylene ether ketone sulfone)s copolymer (SPAEKS- x ) were synthesized by polycondensation reaction of commercial 2, 2-bis(4-hydroxyphenyl)propane, 4, 4′-dichlorodiphenylsulfone, 4, 4′-dihydroxydiphenylether, and 3, 3′disulfonate-4, 4′-difluorobenzophenone. The degree of sulfonation was realized by controlling quantities of the sulfonated monomer. The structure of SPAEKS- x was confirmed by proton nuclear magnetic resonance and Fourier transform infrared instrument. The tough, flexible, and transparent films of SPAEKS- x were obtained by solution casting. These membranes with desired ion-exchange capacity (IEC) values showed good thermal stability and mechanical properties. The proton conductivity of SPAEKS- x with the IEC of 1.44 meq. g −1 is very close to that of Nafion 117 in a temperature range from 20°C to 100°C. SPAEKS- x copolymers, which combine the advantages of the sufficiently high proton transport conductivity and enhanced physical properties, will be the potential alternative materials to Nafion for proton exchange membrane fuel cell.